WOMEN EMPOWERMENT DALAM PENGGUNAAN KB - Dewi Andariya Ningsih (Oksitosin : Jurnal Ilmiah Kebidanan, 2017)
The determination of choice to use KB involves the involvement of a spouse in taking a decision that the majority is still in control by the husband's decision. According to ICPD 1994, the sustainability of KB planning in Indonesia is that women have equal and equal position in determining the option to utilize family planning. In addition, the choice in utilizing contraceptive media is very important to be considered from various factors, namely the couple's factors, health and contraceptive factors.This study is a literature review that tries to analyze the Women Empowerment in use family planning. Sources for conducting this literature review include literature books, theses and systematic search studies of computerized databases. Based on several journals there were two parts of the study of this article that was Women Empowerment and the determination of choice in using KB. Women Empowerment was empowering women in making choices in the use of contraceptive methods. While the determination of choice in using KB is the consideration in the choice of one (only husband or only wife) or the decision was discussed together. Husbands and wives should seek an accurate explanation of contraception especially related to reproductive health so that together participate and obtain equitable utilities from the instructions and family planning facilities In addition, the choice of use of contraceptives is very important to be considered from a variety of factors namely partner factors, health and parts contraception. It is desirable for all couples to promote mutual attention and commitment and regard not gender in determining methods for using family planning and discussing contraceptive and reproductive health issues without any component of preference in discussions or conclusions in KB. Keywords: Women Empowerment, KB decision ABSTRAK Penentuan pilihan untuk mengunakan KB mencakup keterlibatan pasangan dalam mengambil sebuah keputusan yang mayoritas masih di kontrol oleh keputusan suami. Menurut ICPD 1994, keberlangsungan rancangan KB di Indonesia yakni perempuan memiliki posisi yang sebanding dan sejajar dalam penentuan opsi untuk mendayagunakan KB. Selain itu, pilihan dalam memanfaatkan media kontrasepsi sangat penting dipertimbangkan dari berbagai faktor yaitu faktor pasangan, kesehatan serta faktor alat kontrasepsi. Studi ini yakni merupakan tinjauan literatur untuk menganalisis tentang Women Empowerment dalam Penggunaan KB. Sumber untuk melakukan tinjauan literatur ini meliputi buku literatur, tesis dan studi pencarian sistematis database terkomputerisasi. Berdasarkan beberapa jurnal terdapat 2 bagian dari kajian artikel ini yaitu Women Empowerment dan penentuan pilihan dalam menggunakan KB. Women Empowerment yaitu memberdayakan perempuan dalam menentukan pilihan dalam pendayagunaan metode kontrasepsi. Sedangkan penentuan pilihan dalam menggunakan KB yaitu pertimbangan yang di pilih salah satunya (hanya suami atau hanya istri) atau keputusan tersebut didiskusikan bersama. Suami dan istri seharusnya mencari penjelasan yang akurat tentang kontrasepsi terlebih lagi terkait kesehatan reproduksinya sehingga bersama-sama berpartisipasi serta memperoleh utilitas yang sepadan dari petunjuk dan fasilitas KB Selain itu, pilihan menggunaan alat kontrasepsi sangatlah penting dipertimbangkan dari berbagai faktor yaitu faktor pasangan, kesehatan dan bagian alat kontrasepsi. Diharapkan kepada semua pasangan agar meningkatkan perhatian dan komitmen bersama dan tidak memandang gender dalam penentuan metode untuk menggunakan KB serta mendiskusikan permasalahkan kontrasepsi serta kesehatan reproduksi tanpa ada komponen yang menjadi preferensi dalam diskusi maupun penentuan kesimpulan dalam ber- KB. Kata Kunci : Women Empowerment, keputusan KB